Uso de plantas medicinales en la sanación de enfermedades de filiación cultural en la parroquia San Lucas, ruta del Qhapaq-Ñan - Calderón Bravo, Kiana Marbelle (2020)
Ethnobotany is the science that relates human groups to the plant environment, it follows from the study of: ethnology (study of culture) and botany (study of plants). It is in charge of rescuing ancestral knowledge, because a large percentage of the world population and particularly in developing countries use plants to meet the needs of healing. People who practice the use of plants are called Traditional Health Agents (ATS), who through their experience know which plant to use for the healing of diseases of cultural affiliation, being the basis for restoring balance. The present investigation was carried out on the Qhapaq-Ñan route, in the San Lucas parish, its main objective was: "To describe the use of medicinal plants in the healing of diseases of cultural affiliation in the San Lucas parish, the Qhapaq route- Ñan”. Being a descriptive study, with a mixed approach, the sample corresponds to 5 ATS, where it can be identified through semi- structured interviews, which take less than 20 years of practice. Their average ages are over 65 years old and their specialization is Hierbateros. The main diseases of cultural affiliation are: air sickness, gangrene, fright, evil eye and pulsatile; For its healing, scancel, blue mortiño, horsetail, chamomile, lemon balm, rue and fig are used and, to administer them, the oral and topical routes are used, respectively. Key words: Plants, cultural. Healing, balance, pathways